The effect of inspiratory muscle training on the pulmonary function in mixed martial mrts and kickboxing athletes - Alnuman, N.; Alshamasneh, A. (Journal of Human Kinetics, 2022)
Inspiratory muscle training (IMT) has found its way into athletes` routine as a promising way of improving pulmonary function in combination with standard training. The objective of the study was to examine the effects of resistive IMT on the pulmonary function variables in athletes of two combat sports, i.e., mixed martial arts (MMA) and kickboxing. Fourteen kickboxing and 12 MMA male athletes qualified for the study. They were randomly assigned into experimental and control groups. While both groups participated in their standard training, the experimental group additionally participated in IMT which consisted of 30 breaths twice a day for 6 weeks. The pulmonary functions were measured at baseline and after 6 weeks of IMT. The addition of IMT to standard training increased significantly the forced expiratory volume in the first second to vital capacity ratio (FEV1/VC), and the maximum voluntary ventilation (MVV) (p < 0.05) with changes of 5.7%, and 28.6%, respectively, in MMA athletes. The kickboxing group showed no significant changes. The interaction of the sport discipline and IMT intervention yielded a strong significant change in the MVV (F(1, 11) = 14.53, p < 0.01), and FEV1/VC (F(1, 11) = 20.67, p < 0.01) to the benefit of MMA athletes in comparison with kickboxing athletes. Combining resistive IMT for 6 weeks with standard training was effective to improve some pulmonary functions in MMA athletes, but did not lead to additional gains in kickboxing athletes.